2020
DOI: 10.1111/pcmr.12933
|View full text |Cite
|
Sign up to set email alerts
|

Strategies in DNA vaccine for melanoma cancer

Abstract: Cancer is considered as one of the leading causes of human death worldwide. According to the National Centre for Health Statistics (NCHS), over 600,000 people have died of cancer just in the United States in 2019. Moreover, the NCHS reported that there will be approximately more than 90,000 new cases of melanoma in situ of the skin in 2020 (Siegel et al., 2019). However, the World Health Organization (WHO) has predicted that these statistics may be changed by coronavirus disease 2019 (COVID-19) outbreak in 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 102 publications
0
31
0
Order By: Relevance
“…Vaccine platforms include DNA [77], RNA [78], peptides [79] or direct use of DC cells [80], promoting DC activation, and ultimately generating an anti-tumour immune response and immune memory. Factors influencing vaccine efficacy include antigen quality, DC activation, whether induces strong and sustained CD4 + T helper cells and cytotoxic T lymphocyte (CTL) responses, TME infiltration and persistence and maintenance of the immune response [81].…”
Section: Tlr9 and Tumour Vaccinementioning
confidence: 99%
“…Vaccine platforms include DNA [77], RNA [78], peptides [79] or direct use of DC cells [80], promoting DC activation, and ultimately generating an anti-tumour immune response and immune memory. Factors influencing vaccine efficacy include antigen quality, DC activation, whether induces strong and sustained CD4 + T helper cells and cytotoxic T lymphocyte (CTL) responses, TME infiltration and persistence and maintenance of the immune response [81].…”
Section: Tlr9 and Tumour Vaccinementioning
confidence: 99%
“…These vaccines rely on a gene carrier to introduce an encoded exogenous antigen into body cells, and the endogenous expression system of those cells generates the corresponding antigen and then induces a specific cellular immune response to eliminate cancer cells (7). DNA vaccines are essentially bacterial plasmids encoding tumor antigens, which contain two origins of replication: a prokaryotic origin for replication in the bacterium and a eukaryotic origin for replication in the vaccinated host (8). DNA vaccines are able to migrate to the nucleus for replication, transcription, and antigen production, and then stimulate the immune system by interacting with antigens produced on the host cell surface and their presentation on MHC class I and class II complexes (8,9).…”
Section: Nucleic Acid Vaccinesmentioning
confidence: 99%
“…DNA vaccines are essentially bacterial plasmids encoding tumor antigens, which contain two origins of replication: a prokaryotic origin for replication in the bacterium and a eukaryotic origin for replication in the vaccinated host (8). DNA vaccines are able to migrate to the nucleus for replication, transcription, and antigen production, and then stimulate the immune system by interacting with antigens produced on the host cell surface and their presentation on MHC class I and class II complexes (8,9). DNA vaccines usually utilize a plasmid produced in Escherichia coli as the expression vector and are delivered by intramuscular injection, which can not only induce humoral immunity but also promote the proliferation and differentiation of T cells, thereby leading to cellular immune response (10).…”
Section: Nucleic Acid Vaccinesmentioning
confidence: 99%
“…In this study, the cricket paralysis virus internal ribosome entry site (CrPV IRES )-ssRNA was established and administered to mice challenged with murine melanoma cells. The National Center for Health Statistics reported that approximately 90,000 cases of melanoma occur annually in the USA [38]. Melanoma is the most common type of skin cancer, which occurs in melanocytes that produce the melanin responsible for variations in skin color [39].…”
Section: Introductionmentioning
confidence: 99%